Regulatory T cell-like response to SARS-CoV-2 in Jamaican fruit bats (Artibeus jamaicensis) transduced with human ACE2. - Bradly Burke; Savannah M Rocha; Shijun Zhan; Miles Eckley; Clara Reasoner; Amin Addetia; Juliette Lewis; Anna Fagre; Phillida A Charley; Juergen A Richt; Susan R Weiss; Ronald B Tjalkens; et al. (PLoS Pathogens)
Insectivorous Old World horseshoe bats (Rhinolophus spp.) are the likely source of the ancestral SARS-CoV-2 prior to its spillover into humans and causing the COVID-19 pandemic. Natural coronavirus infections of bats appear to be principally confined to the intestines, suggesting fecal-oral transmission; however, little is known about the biology of SARS-related coronaviruses in bats. Previous experimental challenges of Egyptian fruit bats (Rousettus aegyptiacus) resulted in limited infection restricted to the respiratory tract, whereas insectivorous North American big brown bats (Eptesicus fuscus) showed no evidence of infection. In the present study, we challenged Jamaican fruit bats (Artibeus jamaicensis) with SARS-CoV-2 to determine their susceptibility. Infection was confined to the intestine for only a few days with prominent viral nucleocapsid antigen in epithelial cells, and mononuclear cells of the lamina propria and Peyer's patches, but with no evidence of infection of other tissues; none of the bats showed visible signs of disease or seroconverted. Expression levels of ACE2 were low in the lungs, which may account for the lack of pulmonary infection. Bats were then intranasally inoculated with a replication-defective adenovirus encoding human ACE2 and 5 days later challenged with SARS-CoV-2. Viral antigen was prominent in lungs for up to 14 days, with loss of pulmonary cellularity during this time; however, the bats did not exhibit weight loss or visible signs of disease. From day 7, bats had low to moderate IgG antibody titers to spike protein by ELISA, and one bat on day 10 had low-titer neutralizing antibodies. CD4+ helper T cells became activated upon ex vivo recall stimulation with SARS-CoV-2 nucleocapsid peptide library and exhibited elevated mRNA expression of the regulatory T cell cytokines interleukin-10 and transforming growth factor-β, which may have limited inflammatory pathology. Collectively, these data show that Jamaican fruit bats are poorly susceptible to SARS-CoV-2 but that expression of human ACE2 in their lungs leads to robust infection and an adaptive immune response with low-titer antibodies and a regulatory T cell-like response that may explain the lack of prominent inflammation in the lungs. This model will allow for insight of how SARS-CoV-2 infects bats and how bat innate and adaptive immune responses engage the virus without overt clinical disease.